Pressure Pain Sensitivity and Insular Combined Glutamate and Glutamine (Glx) Are Associated with Subsequent Clinical Response to Sham But Not Traditional Acupuncture in Patients Who Have Chronic Pain - Harte, Steven E. (Mary Ann Liebert, Inc., 2013)
BACKGROUND: Clinical trials of acupuncture in chronic pain have largely failed to demonstrate efficacy of traditional over sham acupuncture. However, it should be noted that sham acupuncture is not inert. OBJECTIVE: To determine if experimental-pressure pain assessment and chemical neuroimaging can identify differential responsiveness to sham as opposed to traditional acupuncture. PATIENTS AND INTERVENTION: Fifty patients with fibromyalgia were randomized to either 9 traditional (TA) or sham (SA) acupuncture treatments over a period of 4 weeks. Both participants and assessors were blinded. MAIN OUTCOME MEASURES: The main outcome measures were pressure-pain sensitivity at the thumbnail, insular glutamate+glutamine (Glx), and clinical pain. RESULTS: Patients with low pain sensitivity (LPS), but not with high pain sensitivity (HPS), had a significantly reduced clinical pain response to SA (change in mean [standard deviation (SD)]: HPS −8.65 [7.91]; LPS −2.14 [6.68]; p=0.03). This relationship was not the case for TA (HPS −6.90 [4.51]; LPS −6.41 [9.25]; p=0.88). SA-treated patients who were more sensitive also had greater baseline levels of insular Glx than patients who were less sensitive (Glx mean [SD]: HPS 11.3 [1.18]; LPS 10.2 [0.54]; p=0.04). CONCLUSIONS: Pressure-pain testing may identify patients who are less likely to respond to SA. This effect may relate to the levels of brain excitatory neurotransmitters.